2017
DOI: 10.1021/acs.jchemed.7b00210
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Perceptions of Laboratory Demonstrators’ Responsibilities To Inform the Design of a Laboratory Teacher Development Program

Abstract: Throughout countries such as Ireland, the U.K., and Australia, graduate students who fulfill teaching roles in the undergraduate laboratory are often referred to as "laboratory demonstrators". The laboratory demonstrator (LD) model of graduate teaching is similar to the more commonly known graduate teaching assistant (GTA) model that is prevalent in the United States. While the responsibilities of LDs and GTAs in the undergraduate laboratory are similar, both cohorts experience different recruitment and traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 74 publications
0
29
0
2
Order By: Relevance
“…However, these approaches are at the group level and except for one study do not consider individual students’ emotions and needs [ 40 ] (Table 1 ). This is a missed opportunity as students’ affective learning experiences have been shown to influence their cognitive and psychomotor learning experiences in first year [ 8 , 46 , 47 ]. Furthermore, positive instructor behaviours have been linked to students’ affective learning experiences, which in turn enhance cognitive learning [ 48 ].…”
Section: First‐year Students’ Needs In the Labmentioning
confidence: 99%
See 4 more Smart Citations
“…However, these approaches are at the group level and except for one study do not consider individual students’ emotions and needs [ 40 ] (Table 1 ). This is a missed opportunity as students’ affective learning experiences have been shown to influence their cognitive and psychomotor learning experiences in first year [ 8 , 46 , 47 ]. Furthermore, positive instructor behaviours have been linked to students’ affective learning experiences, which in turn enhance cognitive learning [ 48 ].…”
Section: First‐year Students’ Needs In the Labmentioning
confidence: 99%
“…[ 49 ]. Therefore, it is important that demonstrators are made aware of the extent and influence of students’ emotions and individual needs in the laboratory and their potential role in promoting positive learning experiences [ 8 ]. Flaherty et al found that demonstrators were unaware of the students’ needs across the cognitive, psychomotor and emotional domains and identified this as a barrier to developing their teaching effectiveness [ 8 ].…”
Section: First‐year Students’ Needs In the Labmentioning
confidence: 99%
See 3 more Smart Citations